Indo-Pacific cooperation: What do trade simulations indicate? - Mohammad Masudur Rahman; Chanwahn Kim; Prabir De (Journal of Economic Structures, 2020)
This paper investigates the potential economic effect of "Indo-Pacific" regional economic cooperation and compares with the extended CPTPP. The Computable General Equilibrium (CGE) results show that the quadrilateral alliance between the United States, Japan, Australia, and India shows although a substantial economic gain whilst South and East Asia join with the Indo-Pacific cooperation, the economic benefit would be enormous. The findings also indicate that South and East Asian improved trade facilitation could bring huge gain as a large part of Indo-Pacific trade has remained unrealized. The trade transaction cost is one of the major trading barriers prohibiting the growth of Indo-Pacific intra-regional trade. The study reinforces that improvement in infrastructure and connectivity that leads to less trade transportation costs should be a necessary step to realise Indo-Pacific trade potential.
Keywords: F14; F15; F17; 330; Indo-Pacific; Trade; Regional integration; Trade facilitation; CGE